Vibrational‐vibrational and vibrational‐thermal energy transfers of CO2 with N2 from MIPAS high‐resolution limb spectra. Issue 15 (15th August 2015) - Jurado‐Navarro, Á. A.; López‐Puertas, M.; Funke, B.; García‐Comas, M.; Gardini, A.; Stiller, G. P.; Clarmann, T. von
Abstract: We present a retrieval of several vibrational‐vibrational (V V) and vibrational‐thermal (V‐T) collisional rate coefficients affecting the populations of the CO2 levels emitting at 10, 4.3 and 2.7 μm from high‐resolution limb atmospheric spectra taken by Michelson Interferometer for Passive Atmospheric Sounding (MIPAS). This instrument has a high spectral resolution (0.0625 cm −1 ) and a wide spectral coverage (from 685 to 2410 cm −1 ) that allow measuring and discriminating among the many bands originating the atmospheric 4.3 μm radiance. Also its high sensitivity allows measuring the atmospheric limb emission in a wide altitude range, from 20 to 170 km in its middle and upper atmosphere modes, and hence obtain information on the temperature dependence of the collisional rates. In particular, we retrieve the rate coefficients and their temperature dependence in the 130–250 K range of the following processes: CO 2 ( v d, v 3 ) + N 2 ⇌ CO 2 ( v d, v 3 − 1 ) + N 2 ( 1 ) with v d =2 v 1 + v 2 =2, 3, and 4; CO 2 ( v 1, v 2, l, 1, r ) + M ⇌ CO 2 ( v 1 ′, v 2 ′, l ′, 1, r ′ ) + M with Δ v d = v d ′ − v d = 0 and Δ l = 0; and with Δ v d =0 and Δ l ≠ 0. In addition we have also retrieved the thermal relaxation of CO2 ( v 3 ) into the v 1 and v 2 modes, e.g., CO 2 ( v d, v 3 ) + M ⇌ CO 2 ( v d ′, v 3 − 1 ) + M with Δ v d =2–4 and Δ v 3 =−1 and the efficiency of the excitation of N2 (1) by O( 1 D ). All of them were retrieved with a much better accuracy than were known before. The new rates have very important effects on the atmospheric limb radiance in the 10, 4.3 and 2.7 μm spectral regions (5–8% at 4.3 μm) and allow a more accurate inversion of the CO2 volume mixing ratio in the mesosphere and lower thermosphere from measurements taken in those spectral regions. Key Points: Crucial V‐V and V‐T rates controlling CO2 IR emission have been retrieved These rates are very different from current values and are much more accurate They are important for CO2 measurements in the mesosphere and lower thermosphere